Oral Nutritional Supplementation for the Dietary Management of Malnutrition in Cancer: Study Protocol of A Randomized, Open-Label, Multicentre Clinical Trial - Nadasi, Edit; Cseh, Gellert (International Journal of Innovative Research in Medical Science, 2019)
In cancer, more than 30% of patients die due to cachexia and more than 50% of patients with cancer die with cachexia being present. Patients with cancer cachexia frequently develop a chronic negative energy and protein balance driven by a combination of reduced food intake and metabolic change. Several studies have already demonstrated the usefulness of oral nutritional supplements (ONS) in managing malnutrition of cancer patients. Though increased energy intake is very important in managing cancer-related malnutrition, the source of this extra energy and the presence of anti-inflammatory and immunonutritional components may also play an important role. Here we present the study protocol of a randomized, open-label, multicentre clinical trial aimed to determine whether an ONS composed according to the needs of patients with malignant diseases an ONS composed according to the needs of patients with malignant diseases is more effective than a general product in improving the nutritional status in cancer patients.